Ask the Puppet. Towards Thomas Ligotti, The Conspiracy against the Human Race - Panayotov, Stanimir (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Stanimir Panayotov Title (English): Ask the Puppet. Towards Thomas Ligotti, The Conspiracy against the Human Race Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011) Publisher: Department of Gender Studies, Euro-Balkan Institute Page Range: 145-152 Page Count: 8 Citation (English): Stanimir Panayotov, “Ask the Puppet. Towards Thomas Ligotti, The Conspiracy against the Human Race,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011): 145-152.